2007
DOI: 10.1002/j.2055-2335.2007.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioner Perceptions of Extended Pharmacy Services and Modes of Collaboration with Pharmacists

Abstract: Aims:To explore the perceptions of Australian general practitioners (GPs) towards extended pharmacy services, and to investigate the modes and extent of collaboration between community pharmacists and GPs. Method: Semi-structured face-to-face and telephone interviews were conducted on a purposive sample of GPs from Sydney and surrounding areas. The data were thematically analysed, using qualitative data analysis software. Results: 23/68 (34%) GPs approached, agreed to participate in the interviews. The respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…The results of this study indicate that there is very limited collaboration between GPs and pharmacists in primary care in Australia with most interactions relating to the routine dispensing of prescriptions. This is consistent with previous research which indicated that genuine collaborative relationships between GPs and pharmacists, in the community setting, are lacking (Ferlie & Shortell, 2001; Van et al, 2007).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The results of this study indicate that there is very limited collaboration between GPs and pharmacists in primary care in Australia with most interactions relating to the routine dispensing of prescriptions. This is consistent with previous research which indicated that genuine collaborative relationships between GPs and pharmacists, in the community setting, are lacking (Ferlie & Shortell, 2001; Van et al, 2007).…”
Section: Resultssupporting
confidence: 94%
“…Research has shown that pharmacists and medical practitioners working together in patient care results in positive health outcomes in cholesterol reduction (Tsuyuki et al, 2002), hypertension (McLean et al, 2008), heart failure (Gattis, Hasselblad, Whellan, & O'Connor, 1999), depression (Landers, Blenkinsopp, Pollock, & Grime, 2002) and medication management (McDonough & Doucette, 2003). Although multidisciplinary care plans which coordinate and integrate treatment and care processes delivered by different HCPs are well established in hospital and ambulatory care, the ability of HCPs to collaborate in primary care seems to vary between practitioners and practitioner teams (Brock & Doucette, 2004; Van, Krass, & Mitchell, 2007). Despite attempts over the years to introduce more collaborative models of practice, most HCPs in primary care continue to work as functionally separate solo practitioners (Dieleman et al, 2004;Dobson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…GPs were unlikely to readily give community pharmacists clinical information about their patients. This lack of communication and transfer of clinical patient information between GPs and community pharmacists was also perceived to exist by community pharmacists in a study of their involvement in medication management (Dinnie, Bond, & Watson, 2004;Van et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…It is also unclear whether GP and community pharmacist training incorporates relationship building and team working/collaborative training (Shortell & Kaluzny, 2000;Van et al, 2007). Enhanced training in these areas may thus be beneficial in promoting stronger GP/ community pharmacist relationships, thereby increasing the likelihood of successful GP/community pharmacist collaborative CDM.…”
Section: Concluding Commentsmentioning
confidence: 98%
See 1 more Smart Citation